Phylogeny and molecular evolution analysis of PIN-FORMED 1 in angiosperm. - Pengkai Wang; Tielong Cheng; Shuang Wu; Fangfang Zhao; Guangping Wang; Liming Yang; Mengzhu Lu; Jinhui Chen; Jisen Shi (PLoS ONE)
PIN-FORMED 1 (PIN1) is an important secondary transporter and determines the direction of intercellular auxin flow. As PIN1 performs the conserved function of auxin transport, it is expected that the sequence and structure of PIN1 is conserved. Therefore, we hypothesized that PIN1 evolve under pervasive purifying selection in the protein-coding sequences in angiosperm. To test this hypothesis, we performed detailed evolutionary analyses of 67 PIN1 sequences from 35 angiosperm species. We found that the PIN1 sequences are highly conserved within their transmembrane regions, part of their hydrophilic regions. We also found that there are two or more PIN1 copies in some of these angiosperm species. PIN1 sequences from Poaceae and Brassicaceae are representative of the modern clade. We identified 12 highly conserved motifs and a significant number of family-specific sites within these motifs. One family-specific site within Motif 11 shows a different residue between monocots and dicots, and is functionally critical for the polarity of PIN1. Likewise, the function of PIN1 appears to be different between monocots and dicots since the phenotype associated with PIN1 overexpression is opposite between Arabidopsis and rice. The evolution of angiosperm PIN1 protein-coding sequences appears to have been primarily driven by purifying selection, but traces of positive selection associated with sequences from certain families also seem to be present. We verified this observation by calculating the numbers of non-synonymous and synonymous changes on each branch of a phylogenetic tree. Our results indicate that the evolution of angiosperm PIN1 sequences involve strong purifying selection. In addition, our results suggest that the conserved sequences of PIN1 derive from a combination of the family-specific site variations and conserved motifs during their unique evolutionary processes, which is critical for the functional integrity and stability of these auxin transporters, especially in new species. Finally, functional difference of PIN1 is likely to be present in angiosperm because the positive selection is occurred in one branch of Poaceae.